Effect of Fertilizer (NPK) on Growth Behavior and Biomass Production of Parkia Timoriania (DC.) Merr. and Tamarindus Indica Linn. Seedlings - Upadhyaya, K.; Marak, Thupan R. (Indian Forester, 2014)
The effect of fertilizer (NPK) application on growth and biomass production of Parkia timoriana and Tamarindus indica seedlings was studied in a pot experiment. Fertilizers were applied to the potted seedlings in the form of urea, DAP and muriate of potash in different doses forming five treatments viz. T (Control), T (Urea: DAP: MoP 0.5g: 0.5g: 0.5g), T 0 1 2 (Urea: DAP: MoP 1.0g: 1.0g: 1.0g), T (Urea: DAP: MoP 2.0g: 2.0g: 2.0g), and T (Urea: DAP: MoP 4.0g: 4.0g: 4.0g). 3 4 Fertilizer application showed a negative response on the growth attributes and biomass production of P. timoriana seedlings. On the other hand, NPK application resulted in stimulated growth and biomass of T. indica seedlings and compared to control, the most significant changes were recorded in T2 treatment (Urea: DAP: Muriate of potash 1.0g: 1.0g: 1.0g).